Counterion induced facile self-doping and tunable interfacial dipoles of small molecular electrolytes for efficient polymer solar cells. (September 2016) - Chen, Lie; Tan, Yun; Liu, Xiangfu; Chen, Yiwang
Abstract: Three easily accessible diketopyrrolopyrrole (DPP)-based small molecular electrolytes (SMEs) with different counter anions (CAs), such as bromide, tetrafluoroborate, and tetraphenylborate, namely DPPN-Br, DPPN-BF4, and DPPN-BPh4, respectively, were synthesized to function as a cathode buffer layer for improving the performance of polymer solar cells. Intriguingly, a strong CA size dependence of self-doping was observed in the SMEs. More interestingly, a tunable dipoles were achieved on the ITO surface modified with electrolytes by simply varying the size of CAs, as verified by the significantly reduced effective work function ( Φ eff ). These n-type self-doped electrolytes possessed a higher electron mobility and created Ohmic contact between the ITO and active layer. Notably, an improved power conversion efficiencies (PCE) of 9.0% was achieved in the device with DPPN-BPh4 interlayer. Graphical abstract: Highlights: Counterion dependence of n-type self-doping interfacial dipoles was fine-tuned. Combination of electron mobility and energy alignment was improved. Polymer solar cells with a power conversion efficiency of 9% were obtained.